Why nations fail : the origins of power, prosperity and poverty / Daron Acemoglu and James A. Robinson - Acemoglu, Darson (London, 2013)
Amartya Sen throws the concept of justice under the spot-light by establishing The Idea of Justice as a reason to ponder about how the society is being unjust. It talks about what can be done to make society more fair and the need to realize that tomorrow never comes when it is about seeking justice. In this book, arguments against social evils and words of motivation for what is integral and right for the society are discussed. An epitome of the values contained in the country's Constitution, The Idea of Justice is a beacon of vision that every citizen of the country must see, grow into, achieve and stand-up for. There is integrity, equality, tolerance, benevolence, honesty and power in this book, making it a torch that spreads the light of a nation's belief system.
Keywords: Economic anthropology